4D vertical seismic profile modeling of CO2 injection scenarios to evaluate field results at Aquistore. (May 2018) - Harris, Kyle; White, Don; Samson, Claire; Tao, Jiang
Highlights: Modeled plumes yielded seismic anomalies in partial agreement with those from field. More effort is required to better predict plume shape and location in the future. Strongest CO2 -based anomalies are located in the lower Deadwood formation. Abstract: The Aquistore carbon capture and storage project (Saskatchewan, Canada) is currently employing 3D vertical seismic profiles to monitor CO2 injected in a geological reservoir at a depth of >3200 m. Distributed acoustic sensing has previously been shown to be an effective tool for imaging the CO2 plume at the research site, and this study presents a continued effort in characterizing its trajectory, location, and size via fluid flow simulations, fluid substitution calculations, and forward modeling of seismic data. Time-lapse synthetic seismic volumes corresponding to two injection quantities, 36 and 97 kt, are compared alongside distributed acoustic sensing field data with nearly identical acquisition geometries and processing flows. The modeling results support the interpretation, based on field data, that most of the CO2 signal originates from the lower Deadwood reservoir unit. However, it is apparent that more effort is required to predict the trajectory of the plume, and the seismic amplitude contrasts caused by fluid replacement.